Early initiation of high-volume hemofiltration may reduce complications of high-voltage electrical injuries: A case report - Christopher T. Buckley; Sai R. Velamuri; Ibrahim Sultan-Ali; Faisal Arif; William L. Hickerson; David M. Hill (Elsevier, 2020)
The purpose of this case was to report the impact of early use of high-volume hemofiltration on a previously healthy male admitted after sustaining a high-voltage electrical injury. Initial labs revealed acute kidney injury secondary to rhabdomyolysis with myoglobinuria. The patient required fasciotomies to the three affected extremities and a right above the elbow amputation. Aggressive fluid resuscitation failed to maintain urine output above 20 mL/h. By 24 h, the patient had a 12.8 L positive fluid balance. High-volume hemofiltration was initiated at 60 mL/kg/h using a system with a high cut-off filter for acute kidney injury and volume management. Urine myoglobin was negative by day 3 and serum myoglobin decreased to 221.46 nmol/L. He was extubated on day 5, achieved euvolemia on day 6, and high-volume hemofiltration was discontinued on day 13 with subsequent full renal recovery. He underwent several staged surgeries for burn wound excision and grafting, and the left lower extremity was salvaged. His length of stay was prolonged due to multiple social barriers, but free of sepsis and pneumonia. Early initiation of high-volume hemofiltration with a high cut-off filter helped to expedite removal of acute kidney injury and enable more effective volume management to minimize complications of high-voltage electrical injury and its treatment and likely improve outcomes.